Homogeneous and heterogeneous catalytic ozonation of endosulfan with activated carbon as catalyst - E Enjarlis; Setijo Bismo; S Slamet; Roekmijati W Soemantojo (Jurnal Teknik Kimia Indonesia, 2007)
Homogeneous and heterogeneous  catalytic ozonation of endosulfan with activated carbon as catalystCatalytic ozonation of endosulfan with the presence of activated carbon as catalyst was investigated at neutral pH and different temperatures. The model kinetics was developed based on the mechanism of catalytic decomposition ozone, namely homogeneous and heterogeneous decomposition reaction. This study focuses on determining the contribution of homogeneous and heterogeneous reaction to endosulfan removal in catalytic ozonation with activated carbon as catalyst. Endosulfan was selected as a target of study because it is organic pollutant and organic chlorine pesticide (OCPs) groups that may cause a serious environmental concern. The use of activated carbonfrom Bogar Forest Centre actually provides a slightly contribution in enhancing endosulfan oxidation reaction with ozone. This is because endosulfan has sulfide group or sulfur element that is very reactive to ozone. Even though, the amount of OH increases because of ozonation with activated carbon use. The heterogeneous and homogeneous reaction contributions at  neutral  pH and temperature range of 20- 30oC  were 11-21% and 79- 89% from overall endosulfan removal in catalytic ozonation with promoted by of activated carbon, respectively.Keywords: Activated Carbon, Catalytic Ozonation, Endosulfan AbstrakOzonasi katalitik endosulfan dengan adanya katalis karbon aktif dilakukan pada pH netral dan suhu yang berbeda-beda. Persamaan kinetika reaksi dikembangkan berdasarkan mekanisme reaksi dekomposisi ozon secara katalitik yaitu reaksi homogen dan heterogen. Penelitian ini ditujukan terutama untuk menentukan kontribusi reaksi homogen dan heterogen terhadap penyisihan endosulfan di dalam ozonasi katalitik dengan karbon aktif sebagai katalis.Endosulfan dipilih sebagai sasaran penelitian karena merupakan polutan organik dan kelompok pestisida organoklorida (OCPs) yang menjadi perhatian serius di lingkungan. Karbon aktif yang digunakan berasal dari Balai Hutan Bogar yang ternyata memberikan pengaruh kecil terhadap peningkatan reaksi oksidasi endosulfan dengan ozon. Hal ini disebabkan endosulfan mempunyai gugus sulfida atau sulfur yang sang at reaktif terhadap ozon. Meskipun, jumlah OH meningkat disebabkan penggunaan ozonasi dengan karbon aktf. Kontribusi reaksi homogen dan heterogen terhadap penyisihan endosulfan pada kondisi pH netral dan suhu 20-30 oC  masing-masing sebesar 79- 89% dan 11- 21% dari total penyisihan endosulfan dalam ozonasi katalitik dengan dipromosikan oleh karbon aktifKata kunci: Endosulfan, Karbon Aktif, Ozonasi Katalitik